Physico-chemical limnology of Zoo Negara Lake, Malaysia - M. Yusoff, Fatimah; Sharr, H. A. (Stuttgart : E. Schweizerbart'sche Verlagsbuchhandlung, 1987)
A physico-chemical Iimnological survey on Zoo Negara Lake and its incoming water from the upstream of Kemansah River was carried out from May to October 1981. Generally the water in both the stream and lake is weakly acidic with low alkalinity and low nutrient concentrations. The physical and chemical parameters in the lake are higher than that observed in the upstream reaches of Kemansah River especially in turbidity and total residues. The high turbidity and residues were due-to the high loading of erosion particles resulting from the housing development in the watershed. The lake is threatened by erosion and siltation problems, but it is free from biogenic pollution.